Skill decay following Basic Life Support training: a systematic review protocol - Andrew Owen; Joseph Alderman; Emily Beesley; Jonathan Hulme; Benjamin Stanley; Thomas Burton; Harriet Percival; Nicholas Coffin (BMJ Open)
Introduction Survival from out of hospital cardiac arrest (OHCA) is lower in the UK than in several developed nations. Bystander cardiopulmonary resuscitation (CPR) is associated with increased rates of survival to hospital discharge following OHCA, prompting the introduction of several initiatives by the UK government to increase rates of bystander CPR, including the inclusion of Basic Life Support (BLS) teaching within the English national curriculum. While there is clear benefit in this, increasing evidence suggests poor retention of skills following BLS teaching. The aim of this systematic review is to summarise the literature regarding skill decay following BLS training, reporting particularly the time period over which this occurs, and which components of would-be rescuers’ performance of the BLS algorithm are most affected.Methods and analysis A search will be conducted to identify studies in which individuals have received BLS training and received subsequent assessment of their skills at a later date. A search strategy comprising relevant Medical Subject Headings (MeSH) terms and keywords has been devised with assistance from an experienced librarian. Relevant databases will be searched with titles, abstract and full-text review conducted independently by two reviewers. Data will be extracted from included studies by two reviewers, with meta-analysis conducted if the appropriate preconditions (such as limited heterogeneity) are met.Ethic and dissemination No formal ethical approval is required for this systematic review. Results will be disseminated in the form of manuscript submission to a relevant journal and presentation at relevant meetings. To maximise the public’s access to this review’s findings, any scientific report will be accompanied by a lay summary posted via social media channels, and a press release disseminated to national and international news agencies.PROSPERO registration number CRD42021237233.